The holistic idea as a socio-cultural imperative of the modern general scientific picture of the world - Gorelikov, Lev (Actual Problems of Mind, 2017)
The paper actualizes the problem of the construction of the holistic model of the world reality in the unity of physical, biotic, social and mental processes. The author claims that one can construct such a model on the basis of the logic of self-negation in a progressive promotion of the holistic world.